The Implementation of Halal Supply Chain Management on Processed Meat Products in Yogyakarta - Fitri Eka Aliyanti; Luthfiana Kariim; Yudha Mauluddin (Journal of Islamic Economics Lariba, 2022)
The implementation of Law No. 33/2014 on Undang-Undang Jaminan Produk Halal (UUJPH) has become apparent with establishing Badan Penyelenggara Jaminan Produk Halal (BPJPH/Halal Products Certification Agency). The government plays a significant role in guaranteeing halal products for the community because Muslim consumers cannot validate massive credential halal products. In creating a halal product, it will undergo a process from raw materials to ready-to-consume products. There are eleven criteria for the Halal Assurance System in Indonesia, which become the guidelines for conducting halal product audits. One of them is the traceability aspect. It is the critical point in conducting studies on the halal supply chain. The research aims to explain the implementation of supply chain management in restaurants or stalls in Yogyakarta with halal certification from Majelis Ulama Indonesia (MUI/ Indonesian Ulema Council). It also analyses halal principles in supply chain management on processed meat products among restaurants or stalls in Yogyakarta. Also, it aims to identify problems among entrepreneurs of processed meat products in implementing halal supply chain management. The researchers implemented qualitative research with a descriptive analysis approach. The data were obtained from interviews and observations with entrepreneurs, slaughterhouse owners, and BPJPH. The researchers also conducted Focus Group Discussion (FGD) with the management of LPPOM MUI DIY. The second approaches are the data triangulation methods. Respondents were selected with the purposive sampling method. The data obtained were then analyzed with Atlas.ti software application. The results indicate that the entrepreneurs who have been halal certificated are highly likely apply halal principles in their business lines. Additionally, most entrepreneurs who run a halal business do not have any significant problem implementing halal supply chain management.Keywords: Management, Supply Chain, Halal, Halal Products, Meat